Discourse of the Implementation of International Principles in Cases of Forest Fires in Indonesia - Apristyan, Secondio; Fidhata, Tri Kurnia Agung (Indonesian Journal of Environmental Law and Sustainable Development, 2023)
Forest fires in Indonesia have become a recurring environmental crisis with widespread consequences. International principles and agreements provide frameworks for addressing such disasters, yet the translation of these principles into effective action at the national level remains challenging. This paper conducts a discourse analysis to examine the implementation of international principles in Indonesian forest fire cases. Drawing from policy documents, media reports, and scholarly literature, the study investigates Indonesia's adherence to these principles and the factors influencing their application. Findings reveal a complex landscape of challenges and opportunities. While Indonesia has made commitments to international agreements, such as the United Nations Framework Convention on Climate Change and the ASEAN Agreement on Transboundary Haze Pollution, translating these commitments into tangible policies and actions faces hurdles such as institutional capacity, governance issues, and conflicting interests. Moreover, the discourse surrounding forest fires involves diverse stakeholders, including government agencies, non-governmental organizations, and international bodies, each with varying perspectives and agendas. This research underscores the importance of understanding the dynamics of international environmental governance in addressing transboundary challenges like forest fires. By elucidating the discourse surrounding the implementation of international principles in Indonesian forest fire cases, this study contributes to advancing knowledge on global environmental governance and offers insights for fostering more effective collaboration among stakeholders to mitigate the impacts of future forest fire crises.